Survey-based experiential learning - means of raising professional awareness in developing countries. (13th November 2019) - Hodza-Beganovic, R; Berggren, P; Hugelius, K; Edelbring, S
Abstract: Background: Healthcare in post-war Balkans is still under development. Healthcare changes towards more complex clinical scenarios that need different competencies around patients. This study reports on survey based learning to increasing professional awareness for developing sustainable healthcare settings using an experiential learning approach. Methods: In this study, researchers and educators identified non-technical skills concepts on individual, team, and organizational levels. These concepts were contextualized into the local setting through interactive workshops. Two pediatric surgery clinics in Kosovo and Bosnia and Herzegovina participated who were part of an international clinical skills training project. The tools and surveys were: Johari window, Kolb's learning style questionnaire, team members exchange quality scale, the IPEC framework for interprofessional competence, Team STEPPS observation tool and organizational models. Results: A model is developed for contextualizing core concepts on professional awareness into a local developing healthcare setting. It entails three steps conducted in consecutive workshops: Identifying research-based concepts on professional competence on individual, team and organizational levels. Facilitating local contextualization of these concepts by using surveys in interactive workshops. Agreeing on indicators to maintain high professional awareness. Conclusions: Capacity-building in public health can be conducted through increasing professional awareness. Professional awareness can be approached in individual, team and organizational dimensions. Established core concepts of non-technical skills can be contextualized in other cultures through a survey-based experiential learning approach. Key messages: Professional individual, team and organizational awareness is a vital part of conducting efficient healthcare. The professional awareness can be enhanced through processing core concepts in a local context through facilitated workshops.